Distracted Doctoring : Returning to Patient-Centered Care in the Digital Age - Papadakos, Peter J.; Bertman, Stephen (Springer International Publishing : Imprint: Springer, 2017)
Examining-room computers require doctors to record detailed data about their patients, yet reduce the time clinicians can spend listening attentively to the very people they are trying to help. This book presents original essays by distinguished experts in their fields, addressing this critical problem and making an urgent case for reform, because while electronic technology has revolutionized the practice of medicine, it also poses a unique challenge to health care. Smartphones in the hands of doctors and nurses have become dangerously seductive devices that can endanger their patients. Distracted Doctoring is written for anesthesiologists and surgeons, as well as general practitioners, nurses, and health care administrators and students. Chapters include Electronic Challenges to Patient Safety and Care; Distraction, Disengagement, and the Purpose of Medicine; and Managing Distractions through Advocacy, Education, and Change.
Keywords: Medicine.; Neurosurgery.; Surgery.; elektronické knihy; electronic books